Child mental health problems and poverty - Philip Graham; Barbara Maughan (BJPsych Bulletin)
Waiting lists for children and young people with mental health problems are at an all-time high. Almost the only policies proposed to deal with this situation involve increasing the number of mental health professionals. Little attention is given to dealing with the underlying causative stresses, of which poverty is easily the most pervasive. It is suggested that unless levels of poverty are reduced, the rates of psychiatric disorders will not change. As psychiatrists, we need to become much more active in pressing for action over child poverty.